Powers as the Fundamental Entities in Philolaus' Ontology - Viltanioti, Irini Fotini (Journal of Ancient Philosophy, 2012)
The main claim of this paper is that powers are the fundamental entities in Philolaus’ ontology.Limiters () and unlimiteds ( ι) are to be respectively understood as the power tolimit and the power to be limited. As powers to do something, limiters and unlimiteds aredifferent from their individual bearers, namely the “things that are” (). Number or harmony,that is the power to fit together, makes, along with the basic powers to limit and to be limited,things what they are. Philolaus’ ι should be understood as the outcome of the working of thethree other powers, namely , ι and μ, coming together and coming to berealized (μ). In other words, ι is the state that results from the realization of the threefundamental powers. Philolaus’ are to be considered as coming out of the four primarypowers and of what Philolaus refers to as . Thus, Philolaus appears to be one of the firstpower structuralists.